2022
DOI: 10.1056/nejmoa2116063
|View full text |Cite
|
Sign up to set email alerts
|

Covid-19 Vaccine Effectiveness in New York State

Abstract: Background Population-based data from the United States on the effectiveness of the three coronavirus disease 2019 (Covid-19) vaccines currently authorized by the Food and Drug Administration are limited. Whether declines in effectiveness are due to waning immunity, the B.1.617.2 (delta) variant of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), or other causes is unknown. Methods We used data for 8,690,825 adults in New York State to assess the effect… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
261
5
4

Year Published

2022
2022
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 275 publications
(285 citation statements)
references
References 15 publications
15
261
5
4
Order By: Relevance
“…Looking at vaccine types, the reduction in vaccine effectiveness is apparent for both Moderna and Pfizer-BioNtech. We thus find some direct but inconclusive evidence of a moderate waning of mRNA vaccine effectiveness against hospitalization after 25 weeks, which is in agreement with data from Israel [19], Qatar [20] and New York state [21]. However, our findings are in contrast with other studies that showed considerably faster waning among older individuals after more than 6 months [22].…”
Section: Discussionsupporting
confidence: 85%
“…Looking at vaccine types, the reduction in vaccine effectiveness is apparent for both Moderna and Pfizer-BioNtech. We thus find some direct but inconclusive evidence of a moderate waning of mRNA vaccine effectiveness against hospitalization after 25 weeks, which is in agreement with data from Israel [19], Qatar [20] and New York state [21]. However, our findings are in contrast with other studies that showed considerably faster waning among older individuals after more than 6 months [22].…”
Section: Discussionsupporting
confidence: 85%
“…The overall reduction of 31.7% per month (95% CI: 29.4-33.9%) we observed in our study closely agrees with a previous longitudinal study that investigated waning of antibody levels in 1,647 health care workers after the second dose of a mRNA COVID-19 vaccine [8], but is slightly less than the 18.3-fold decrease reported in 3,808 health care workers six months after receipt of dose two of the BNT162b2 vaccine [9], The minimal antibody level however that is required for preventing a SARS-CoV-2 infection or for preventing severe COVID-19 as well as the importance of cell-mediated immunity is still unclear [19,20]. Nevertheless, our findings support the notion that effectiveness of COVID-19 vaccines is reduced after 4-6 months [21][22][23] and that a booster dose is needed to reinstate the protection conferred by the vaccines [19].…”
Section: Discussionsupporting
confidence: 72%
“…Observational studies from Qatar (n=231 826) 15 and Kaiser Permanente (n=3 436 957) 16 reported vaccine efficacy of more than 90% in preventing hospital admissions during delta-variant transmission, even up to 6 months after vaccination. Observational data from the state of New York, USA (n=8 834 604) indicated high vaccine efficacy in preventing severe disease in people older than 65 years, with varying levels of protection conferred by different vaccines-95% for BNT162b2, 97% for mRNA-1273, and 86% for Ad26.COV2.S 17 -with minimal declines in protection 6 months after vaccination.…”
mentioning
confidence: 99%